THE RELATIONSHIP BETWEEN LECTURERS’ PERCEPTIONS OF THEIR LEADERSHIP CAPACITY AND ORGANIZATIONAL CULTURE AT STRATEGY FIRST UNIVERSITY, YANGON, MYANMAR - THEINGI AUNG; YE, YAN (Scholar: Human Sciences, 2022)
This study examines the relationship between lecturers’ perceptions of leadership capacity and organizational culture at Strategy First University, Yangon, Myanmar, in the 2020 academic year. A total number of 70 lecturers who were currently teaching Undergraduate and Professional development degrees at the university were surveyed. The researcher conducted the study using High Leadership School Survey (HLCSS) by Lambert (2003) and Organizational Culture Survey adopted from Denison (1990). The collected data were analyzed with descriptive statistics, and the Pearson Product Moment Correlation was used to determine the relationship between the two variables. The study showed a moderate relationship between lecturers’ perceptions of their leadership capacity and organizational culture, r (68) =.47, p=.000 according to APA standards. The lecturers’ leadership capacity could be enhanced by participation in teamwork, communication with each other, involvement in decision-making processes, and cooperation with stakeholders to strengthen their leadership capacity. It was recommended that lecturers spend more time on participation, collaborative work, and reflection for their professional development. The administrators should practice shared leadership and arrange organizational learning for lecturers to assess their practices and make required changes in line with the changing educational environment.